Chemical and biological study of essential oils from Eugenia pruniformis Cambess., an endemic species from Brazilian Atlantic Forest - Albuquerque, Ricardo D. D. G. (2012)
Eugenia pruniformis Cambess. is an endemic species from Brazilian Atlantic Forest. Essential oils from leaves and fruits from this species were obtained by hydrodistillation and analyzed by GCMS/CG-FID. In all, 25 compounds were identified, with predominance of sesquiterpene hydrocarbons in both plant parts. The major compounds were β-caryophyllene, bicyclogermacrene, germacrene D, δ- cadinene and α-copaene. Antioxidant activity was performed for essential oil from leaves using ORAC method, showing value of 0.30 ± 0.06 mmol TE/g. Anticholinesterasic evaluation was also performed for this oil, indicating that it inhibited acetylcholinesterase, showing an IC50 of 1798 μg/mL. These results indicate that this essential oil may be considered as a potential source of substances for Alzheimer’s disease Treatment. To our knowledge, these are the first contributions to biological and phytochemical characterization of E. pruniformis, an almost unexplored species from Brazilian Atlantic Forest.